Beyond Neighborhood Quality: The Role of Residential Instability, Employment Access, and Location Affordability in Shaping Work Outcomes for HOPE VI Participants. Issue 4 (2nd September 2016) - Nguyen, Mai Thi; Webb, Michael; Rohe, William; Noria, Estefany
Abstract: This article examines the relationship between neighborhood quality, residential instability, employment access, location affordability, and work outcomes among individuals relocated as part of the Boulevard Homes HOPE VI redevelopment in Charlotte, North Carolina. We found that, contrary to expectations, relocation to private-market units with vouchers, as compared with public housing, did not always result in better neighborhood outcomes. Whereas voucher holders relocated to better quality neighborhoods, relocatees who moved to other public housing lived in neighborhoods with better employment access and lower costs. We also found a positive correlation between locational affordability (housing + transportation costs) and work outcomes.